MODELING OF TRANSPORT PROCESSES IN THE FORMATION AND DEVELOPMENT OF CROSS-BORDER INFRASTRUCTURE - Roman G. Korol (International Journal of Advanced Studies, 2024)
The increase in the volume of Russia's foreign trade turnover with the countries of the Asia-Pacific region requires the rapid development of cross-border infrastructure. The workload of the port facilities of the Pacific basin negatively affects the efficiency of processing and passing transport and cargo flows, therefore, the formation of a new and development of the existing transport and terminal logistics infrastructure of land-based cross-border crossings is underway. The article proposes the infrastructural development of a cross-border crossing by organizing transport and logistics facilities of an adjacent type of transport. An integrated approach to strengthening the throughput and processing capacity of border checkpoints within the framework of the international transport corridor will ensure the consistent development of cross-border transport and logistics facilities, taking into account economic assessment. One of the methods of substantiating the options for infrastructural and technological development of a cross-border transition is simulation modeling, which allows analyzing and predicting the behavior of transport and logistics facilities under the influence of environmental factors.